La alimentación saludable como factor clave en el desarrollo integral de los niños de educación inicial, Machala (2024) - Matamoros Gallardo, Rosa Emilia; Quevedo Medina, Yarlin Lissbeth (Machala: Universidad Técnica de Machala, 2025)
The degree project entitled “Healthy Eating as a Key Factor in the Integral Development of Preschool Children” emerges from the need to promote proper eating habits at the preschool level, following the observation that the snacks brought by students lack sufficient nutritional value and do not contribute positively to their development. The purpose of the research was to describe how healthy eating influences the integral development of preschool-aged children. To this end, a quantitative methodology was applied, using a non-experimental, descriptive research design, along with tools such as observation sheets, checklists, and surveys, applied to a population consisting of 44 parents and 44 children. The findings revealed inconsistencies between what legal guardians express about healthy eating and the actual dietary practices of the students, who consume foods that are either low in nutritional quality or unbalanced in composition—products that merely satisfy hunger without offering any meaningful benefit. These patterns reflect inappropriate eating behaviors, with negative implications for the student population. In response to this situation, a food guide was developed, which includes a sample menu, a classification of food groups, and practical recommendations to improve the nutritional quality of school meals. The proposal was evaluated in terms of technical, economic, social, and environmental feasibility, leading to the conclusion that its implementation is both viable and beneficial for the entire educational community and families. The guide is intended to serve as an educational and preventive tool that supports the comprehensive development of children through balanced nutrition from early childhood onward.
El proyecto de titulación denominado “La alimentación saludable como factor clave en el desarrollo integral de los niños de educación inicial” se manifiesta por la necesidad de fomentar hábitos alimenticios adecuados en a nivel preescolar, tras evidenciarse que los refrigerios presentan escaso valor nutricional y no favorecen su desarrollo. La investigación tuvo como finalidad describir como la alimentación saludable influye en el desarrollo integral en los niños de educación inicial. Para ello, se aplicó una metodología de enfoque cuantitativo, con un diseño no experimental de tipo descriptivo, utilizando herramientas como ficha de observación, lista de cotejo y encuesta; a una población compuesta por 44 padres y 44 niños. Los hallazgos revelaron discrepancias entre el discurso de los representantes legales y las prácticas alimentarias reales en los estudiantes, quienes ingieren alimentos de baja calidad nutricional o desbalanceados en este aspecto, pues solo sacian el hambre más no aportan ningún otro beneficio, denotando conductas impropias en lo que a nutrición se refiere, repercutiendo negativamente en la población estudiantil. En respuesta, se diseñó una guía alimentaria, que contempla un menú, la clasificación de los grupos alimenticios y sugerencias prácticas para mejorar la calidad nutricional en el entorno escolar. La propuesta fue evaluada en términos de factibilidad técnica, económica, social y ambiental, concluyéndose que su aplicación es viable y beneficiosa para toda la comunidad educativa y las familias. Esta guía se propone como una herramienta educativa y preventiva para favorecer el desarrollo integral infantil a través de una alimentación equilibrada desde los primeros años.
Keywords: ALIMENTACIÓN SALUDABLE; DESARROLLO INTEGRAL; EDUCACIÓN INICIAL; GUÍA ALIMENTARIA